Fiber Optic Phase-Based Sensor for Detection of Axles and Wheels of Tram Vehicles - Jan Nedoma; Michal Kostelansky; Michael Fridrich; Jaroslav Frnda; Miroslav Pinka; Radek Martinek; Martin Novak; Stanislav Zabka (Communications - Scientific letters of the University of Zilina, 2020)
This paper presents a novelty approach to usage of the fiber-optic phase-based sensor in railway transportation. We designed and tested the real deployment of this sensor working on the principle of light interferences within optical fibers. The proposed construction of the sensor allowed to increase the sensitivity and thanks to this can be detected and calculated individual axles and wheels of tram vehicles. We performed long-time period measurements (April to September 2019) in diverse climatic conditions, including measurements of 642 tram passages (several different construction types) in real urban traffic. The detection accuracy level was slightly above 99.4 %.